The Influence of Students' Democratic Freedom on Satisfaction with the Implementation of the 2024 Elections - Sholihah, Hana Naf'atun; Wiraditya, Ganang Aqshel; Silaban, Rebecca Aurelia; Safitri, Dini (JURNAL TAPIS, 2024)
The organization of the 2024 elections is considered quite satisfactory. This is due to the existence of democratic freedom in its implementation. Democratic freedom is one of the things that will play a major role in the satisfaction of organizing the 2024 elections. This article was conducted regarding the effect of students' democratic freedom on their satisfaction with the holding of elections. The relationship between this and democratic freedom has become a research issue. This research method is an explanatory survey. In this study, Slovin's formula was used to calculate the population size. The population of this study amounted to 215 respondents and the survey sample was 68 respondents. Data collection was carried out using a questionnaire in the form of Google Forms and using simple random sampling survey techniques to obtain relevant results. Validity and reliability tests were used for the quantitative analysis of this study. The results of data analysis show that democratic freedom has a significant effect on the satisfaction of organizing the 2024 elections, obtained F count> F table, namely 52,081> 1,997, at the 5% significance level. A correlation level of 0.664 was obtained so that it could be formulated with a percentage count of 44.1%. So the contribution of democratic freedom to the satisfaction of organizing the 2024 elections of UNJ communication science students is 44.1% and the remaining 55.9% is influenced by other variables besides the variables in this study.